LaxCe (1-x) O (2-0.5 x) hollow microsphere and preparation method thereof

Preparation of LaxCe(1-x)O(2-0.5x) hollow microspheres through spray granulation method, solving the problems of complex process, high cost and reduced performance in the prior art, and realizing the industrial production of oxidized rare earth hollow microspheres and performance improvement.

CN119430262APending Publication Date: 2025-02-14HANGZHOU RULIN NEW MATERIALS CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411559303.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The prior art has complex processes and high costs when preparing oxidized rare earth hollow microspheres, and the inorganic templates lead to a degradation in the performance of oxidized rare earth hollow microspheres, making it difficult to achieve industrial application.

Method used

LaxCe(1-x)O(2-0.5x) hollow microspheres were prepared by spray granulation. By controlling the pH value of the slurry and adding dispersant, the negative charge on the surface of the particles was sufficient to cause repulsion and form a well-dispersed slurry. and hollow microspheres are formed by spray drying.

Benefits of technology

The industrial production of oxidized rare earth hollow microspheres has been realized, which reduces production costs, simplifies the process, and improves the performance and application prospects of microspheres.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430262A_ABST
    Figure CN119430262A_ABST
Patent Text Reader

Abstract

The invention discloses LaxCe (1-x) O (2-0.5 x) hollow microspheres and a preparation method thereof, and belongs to the field of rare earth metallurgy. The LaxCe (1-x) O (2-0.5 x) hollow microspheres are prepared by grinding LaxCe (1-x) O (2-0.5 x) (x = 0, 0.36, 0.5) powder, performing spray granulation and performing high-temperature firing. The slurry for spray granulation is high in concentration and good in dispersity, the production cost of spray granulation is reduced, and the yield of hollow microspheres is increased; the prepared LaxCe (1-x) O (2-0.5 x) hollow microspheres have the advantages of light weight, heat insulation, sound insulation and excellent low-frequency performance, and have good application prospects in the fields of reflective thermal insulation coatings, light thermal insulation materials, thermal spraying thermal insulation and wear-resistant materials, thermal insulation plates, sewage purification, sound absorption materials, drug sustained-release and controlled-release bodies, catalyst carriers, photoelectric materials and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a La x Ce (1-x) O (2-0.5x) The invention relates to hollow microspheres and a preparation method thereof, belonging to the field of rare earth metallurgy. Background Art

[0002] La x Ce (1-x) O (2-0.5x) (x=0,0.36,0.5) is a rare earth oxide with a fluorite structure, which has excellent properties such as high thermal stability, chemical stability, good biocompatibility and corrosion resistance.

[0003] Hollow rare earth oxide microspheres are a new type of structural material with properties such as low density, high specific surface area, high activity and surface permeability. They show broad application prospects in the fields of catalysts, coatings, microreactors, sustained and controlled drug release, optoelectronic materials, etc. At present, the synthesis of hollow rare earth oxide microspheres usually uses the template method. Commonly used organic templates include polymer microspheres such as polyacrylamide, polymethyl methacrylate (PMMA), and polystyrene (PS), and inorganic templates include carbon spheres, SiO2, CaCO3 and other microspheres. The surface of the organic template microspheres is coated with rare earth compounds by precipitation, and the template is removed by high-temperature calcination to obtain hollow rare earth oxide microspheres. The hollow rare earth oxide microspheres synthesized by this method have high uniformity and controllable microsphere diameters, but the process is complex and costly, which is not conducive to industrial application. Inorganic microspheres SiO2 and CaCO3 are used as templates, and the surface of the microspheres is coated with rare earth compounds by precipitation method. The templates are removed by high-temperature calcination and acid-base etching to obtain hollow rare earth oxide microspheres. The silicon or calcium content in the rare earth oxide that constitutes the microsphere shell is relatively high, which reduces the performance of the hollow rare earth oxide microspheres. Carbon balls can be used as templates to prepare hollow rare earth oxide microspheres with superior performance, but the high market price of carbon balls limits the application areas of hollow rare earth oxide microspheres.

[0004] Spray granulation is a commonly used powder preparation technology in industry. In the field of rare earth metallurgy, this technology mainly produces solid rare earth oxide balls. However, the preparation of hollow rare earth oxide microspheres by spray granulation has strict restrictions on its dispersibility in the slurry. The dispersion stability of rare earth oxide in the slurry is greatly affected by the zeta potential, particle size, content, dispersant, pH, etc. of various rare earth oxides. The key technology is to select appropriate process parameters for different rare earth oxide zeta potentials to prepare stable and dispersed slurries. Only highly dispersed slurries can be used to prepare hollow structural materials through spray granulation. According to La x Ce (1-x) O (2-0.5x)The special functional development of the spray granulation method to prepare the hollow structure will have good application prospects in the fields of reflective insulation coatings, lightweight thermal insulation materials, thermal spray insulation and wear-resistant materials, insulation panels, sewage purification, sound-absorbing materials, drug sustained-release controlled-release bodies, catalyst carriers, optoelectronic materials, etc. Summary of the invention

[0005] In view of this, the purpose of the present invention is to overcome the shortcomings of the prior art and provide a La x Ce (1-x) O (2-0.5x) Preparation method of hollow microspheres: La was prepared by spray granulation x Ce (1-x) O (2-0.5x) Hollow microspheres will provide an industrial production technology for the application of hollow rare earth oxide microspheres in reflective insulation coatings, lightweight refractory materials, thermal insulation materials and sound-absorbing materials.

[0006] The purpose of the present invention is achieved through the following technical solutions:

[0007] In a first aspect, the present invention provides a La x Ce (1-x) O (2-0.5x) A method for preparing hollow microspheres comprises the following steps:

[0008] 1) Slurry preparation: deionized water, dispersant and La x Ce (1-x) O (2-0.5x) The powders are mixed and ground, and the pH value of the system is maintained during the grinding process. After the grinding is completed, a binder is added and dispersed at high speed to obtain the slurry required for spray granulation;

[0009] 2) Preparation of hollow microspheres: The slurry is uniformly transported to a spray granulator for spray granulation, and the hollow microspheres are collected and then burned to obtain La x Ce (1-x) O (2-0.5x) Hollow microspheres.

[0010] According to a preferred embodiment of the present invention, the dispersant in step 1) is ammonium polyacrylate, and the pH of the system is maintained at 9 during the grinding process.

[0011] According to a preferred embodiment of the present invention, the grinding process is stopped when the powder particle size is less than 500 nm.

[0012] According to a preferred embodiment of the present invention, the La x Ce (1-x) O (2-0.5x) Powder is CeO2, La 0.36 Ce 0.64 O 1.82and one of La2Ce2O7.

[0013] According to a preferred embodiment of the present invention, in step 1), the binder is one of polyvinyl alcohol (PVA) and octylphenol polyoxyethylene ether (Triton X-100).

[0014] According to a preferred embodiment of the present invention, La x Ce (1-x) O (2-0.5x) The mass ratio of powder, deionized water and dispersant is 1:0.5-1:0.001, La x Ce (1-x) O (2-0.5x) The mass ratio of powder to PVA is 1:0.02, La x Ce (1-x) O (2-0.5x) The mass ratio of powder to TritonX-100 is 1:0.06.

[0015] According to a preferred embodiment of the present invention, in step 2), the inlet temperature of the spray granulator is controlled at 110°C-130°C.

[0016] According to a preferred embodiment of the present invention, in step 2), the calcination temperature of CeO2 is 800°C, and the La 0.36 Ce 0.64 O 1.82 And the calcination temperature of La2Ce2O7 is 1000℃-1200℃.

[0017] In a second aspect, the present invention provides La prepared by the method x Ce (1-x) O (2-0.5x) Hollow microspheres, the La x Ce (1-x) O (2-0.5x) The bulk density of hollow microspheres is 1.30-1.35g / cm 3 , particle size D 50 The wall thickness is 15-25μm, the wall thickness is 100-150nm, the compressive strength is 4.5-6.5Mpa, and the room temperature thermal conductivity is 0.05-0.06W / (m·K).

[0018] The core of the method of the present invention is:

[0019] 1) The point where the zeta potential is zero is called the isoelectric point (IEP). At this pH value, the electrostatic repulsion is zero and the solid particles in the suspension gather together. When pH>IEP, the surface charge of the solid particles is negative and the particles repel each other, causing the suspension to remain dispersed. x Ce (1-x) O (2-0.5x)The isoelectric point pH value of the powder particles is 6.75-7.60, and the pH value of the grinding suspension is controlled to be 9, the purpose is to stay away from the pH zone of the IEP value and increase the zeta potential, La x Ce (1-x) O (2-0.5x) The negative charge on the particle surface is sufficient to cause repulsion between particles, thereby preparing a well-dispersed slurry. When the pH of the suspension is greater than 10, the ionic strength of the suspension is increased, the stability of the suspension is strongly affected, and the dispersibility of the suspension is reduced; 2) In order to increase La x Ce (1-x) O (2-0.5x) In the suspension, an anionic dispersant ammonium polyacrylate with a carboxylic acid group is added. When the pH of ammonium polyacrylate in the solution is greater than 8.5, COO - The groups are completely dissociated, so the pH value of the ground suspension is adjusted to 9; 3) Since the maximum saturation capacity of the powder adsorbing the dispersant decreases with the increase of pH, when the pH value of the suspension is 9, the surface charge of the particles is negative, and COO - The groups are completely dissociated, so the adsorption of dispersants on the particle surface only occurs on a few positive sites. The saturation capacity of particles for adsorbing dispersants is low. When excessive dispersants are added, the excessive dispersants cause an increase in the ionic strength of the suspension, destroying the stability of the suspension, so the amount of dispersant added is controlled; 4) During the spray drying process of the slurry with good dispersibility, due to the action of capillary forces, the particles and binder migrate to the surface of the droplets and form a rigid shell on the surface of the droplets, resulting in the formation of hollow particles.

[0020] The advantages and effects of the present invention are:

[0021] (1) La prepared by the present invention x Ce (1-x) O (2-0.5x) Hollow microspheres are lightweight, heat-insulating, sound-insulating, and have excellent low-frequency performance. They will have good application prospects in the fields of reflective insulation coatings, lightweight thermal insulation materials, thermal spray insulation and wear-resistant materials, insulation panels, sewage purification, sound-absorbing materials, drug sustained-release controlled-release bodies, catalyst carriers, and optoelectronic materials.

[0022] (2) The slurry prepared by the present invention contains La x Ce (1-x) O (2-0.5x) The high powder concentration reduces the evaporation of water during the spray granulation process, increases the ability to produce hollow microspheres, and reduces energy consumption;

[0023] (3) The present invention adopts spray granulation technology to prepare CeO2, La 0.36 Ce 0.64 O 1.82Compared with the reported template method production process of La2Ce2O7 hollow microspheres, the production process is simple, green and environmentally friendly, with low production cost, and is easy to realize industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is the SEM image of CeO2 hollow microspheres prepared in Example 1 of the present invention.

[0025] Figure 2 La prepared in Example 2 of the present invention 0.36 Ce 0.64 O 1.82 SEM image of hollow microspheres.

[0026] Figure 3 This is the SEM image of La2Ce2O7 hollow microspheres prepared in Example 3 of the present invention.

[0027] Figure 4 This is the SEM image of CeO2 hollow microspheres prepared in Comparative Example 1 of the present invention.

[0028] Figure 5 The La prepared in Comparative Example 2 of the present invention 0.36 Ce 0.64 O 1.82 SEM image of hollow microspheres.

[0029] Figure 6 This is the SEM image of La2Ce2O7 hollow microspheres prepared in Comparative Example 3 of the present invention.

[0030] Figure 7 This is the SEM image of La2Ce2O7 hollow microspheres prepared in Comparative Example 4 of the present invention. DETAILED DESCRIPTION

[0031] The present invention is further described and illustrated below in conjunction with specific embodiments. The embodiments are merely exemplary of the present disclosure and do not define the scope of limitation. The technical features of each embodiment of the present invention may be combined accordingly without conflicting with each other.

[0032] Example 1

[0033] (1) Preparation of CeO2 slurry: 100 L of deionized water and 0.1 kg of ammonium polyacrylate were added to the dispersion tank of the grinder. After stirring and dispersing evenly, the grinder was turned on and 100 kg of CeO2 powder was gradually added. The pH value of the suspension was controlled at 9 during the grinding process. When the particle size of the powder in the suspension was less than 500 nm, the grinding was stopped and the suspension was transported to the spray granulation dispersion tank. 2 kg of PVA was added and after high-speed dispersion, a spray granulation slurry containing 49.48% CeO2 was obtained.

[0034] (2) Preparation of CeO2 hollow microspheres: The spray granulator was turned on, and the inlet temperature was controlled at 110°C. The slurry was uniformly conveyed into the spray granulator, and the hollow microspheres were collected in a collector. The hollow microspheres were then calcined at 800°C to obtain CeO2 hollow microspheres. Figure 1 The SEM image of the CeO2 hollow microspheres of this example shows that the surface of the obtained CeO2 hollow microspheres is smooth and flat, and the spherical particles are monodispersed without collapse or breakage.

[0035] The obtained CeO2 hollow microspheres were characterized, and the bulk density was tested by the measuring cylinder method, the particle size was tested by BT-9300ST laser particle size analyzer, the wall thickness was tested by focused ion beam scanning electron microscope, the compressive strength was tested by powder compressive strength test method (GB / T-43091-2023), and the room temperature thermal conductivity was tested by Hot Disk method / transient flat plate heat source method.

[0036] (3) Index: The bulk density of the prepared CeO2 hollow microspheres is 1.34 g / cm 3 , particle size D 50 The wall thickness is 18.8μm, the wall thickness is 105nm, the compressive strength is 4.80Mpa, and the room temperature thermal conductivity is 0.06W / (m·K).

[0037] Example 2

[0038] (1)La 0.36 Ce 0.64 O 1.82 Slurry preparation: Add 100L of deionized water and 0.2kg of ammonium polyacrylate into the dispersion tank of the grinder, stir and disperse evenly, then turn on the grinder and gradually add 200kg of La 0.36 Ce 0.64 O 1.82 The pH value of the suspension was controlled at 9 during the grinding process. When the particle size of the powder in the suspension was less than 500 nm, the grinding was stopped and the suspension was transported to the spray granulation dispersion tank. 12 kg of Triton X-100 was added and dispersed at high speed to obtain a granulated powder containing 64.06% La. 0.36 Ce 0.64 O 1.82 Spray granulation slurry.

[0039] (2)La 0.36 Ce 0.64 O 1.82 Preparation of hollow microspheres: Turn on the spray granulator, control the inlet temperature at 120°C, transport the slurry to the spray granulator at a uniform speed, collect the hollow microspheres in the collector, and then burn them at 1000°C to obtain La 0.36 Ce 0.64 O 1.82 Hollow microspheres. Figure 2For this embodiment La 0.36 Ce 0.64 O 1.82 SEM image of hollow microspheres. As can be seen from the figure, the obtained La 0.36 Ce 0.64 O 1.82 The hollow microsphere particles are monodisperse, no collapse is observed, and the surface of the microspheres is slightly rough.

[0040] For the income 0.36 Ce 0.64 O 1.82 The hollow microspheres were characterized using the same characterization and testing methods as in Example 1.

[0041] (3) Index: prepared La 0.36 Ce 0.64 O 1.82 The bulk density of hollow microspheres is 1.33 g / cm 3 , particle size D 50 The wall thickness is 21.4μm, the wall thickness is 128nm, the compressive strength is 5.39Mpa, and the room temperature thermal conductivity is 0.05W / (m·K).

[0042] Example 3

[0043] (1) Preparation of La2Ce2O7 slurry: 100 L of deionized water and 0.15 kg of ammonium polyacrylate were added to a grinder dispersion tank. After stirring and dispersing evenly, the grinder was turned on and 150 kg of La2Ce2O7 powder was gradually added. The pH value of the suspension was controlled at 9 during the grinding process. When the particle size of the powder in the suspension was less than 500 nm, the grinding was stopped and the suspension was transported to a spray granulation dispersion tank. 3 kg of PVA was added and after high-speed dispersion, a spray granulation slurry containing 59.25% La2Ce2O7 was obtained.

[0044] (2) Preparation of La2Ce2O7 hollow microspheres: The spray granulator was turned on, and the inlet temperature was controlled at 130°C. The slurry was uniformly conveyed into the spray granulator, and the hollow microspheres were collected in a collector. The hollow microspheres were then calcined at 1200°C to obtain La2Ce2O7 hollow microspheres. Figure 3 The SEM image of the La2Ce2O7 hollow microspheres of this example shows that the surface of the obtained La2Ce2O7 hollow microspheres is smooth and flat, the spherical particles are monodisperse, and no collapse or breakage is observed.

[0045] The obtained La2Ce2O7 hollow microspheres were characterized using the same characterization and testing methods as in Example 1.

[0046] (3) Index: The bulk density of the prepared La2Ce2O7 hollow microspheres is 1.30 g / cm 3 , particle size D 50The wall thickness is 20.9μm, the wall thickness is 148nm, the compressive strength is 6.13Mpa, and the room temperature thermal conductivity is 0.05W / (m·K).

[0047] Comparative Example 1

[0048] (1) Preparation of CeO2 slurry: The pH value of the suspension is controlled at 4 instead of 9, and the rest is the same as in Example 1 (1).

[0049] (2) Preparation of CeO2 hollow microspheres: same as (2) in Example 1. Figure 4 The SEM image of the CeO2 hollow microspheres of this comparative example shows that the CeO2 hollow microsphere structure is not obtained, and the particles are in a collapsed hemispherical shape.

[0050] Comparative Example 2

[0051] (1)La 0.36 Ce 0.64 O 1.82 Slurry preparation: 20 kg of Triton X-100 replaces 12 kg of Triton X-100, and the rest is the same as in Example 2 (1).

[0052] (2)La 0.36 Ce 0.64 O 1.82 Preparation of hollow microspheres: same as in Example 2 (2). Figure 5 For this comparative example La 0.36 Ce 0.64 O 1.82 SEM image of hollow microspheres. As can be seen from the figure, the obtained La 0.36 Ce 0.64 O 1.82 The particles are monodisperse, but the hollow microspheres show pores and ruptures.

[0053] Comparative Example 3

[0054] (1) Preparation of La2Ce2O7 slurry: 0.3 kg of ammonium polyacrylate replaces 0.15 kg of ammonium polyacrylate, and the rest is the same as in Example 3 (1).

[0055] (2) Preparation of La2Ce2O7 hollow microspheres: same as (2) in Example 3. Figure 6 The SEM image of the La2Ce2O7 hollow microspheres of this comparative example shows that the obtained La2Ce2O7 hollow microspheres have craters, pores, cracks and bonding between particles.

[0056] Comparative Example 4

[0057] (1) Preparation of La2Ce2O7 slurry: 4.5 kg of PVA replaces 3 kg of PVA, and the rest is the same as in Example 3 (1).

[0058] (2) Preparation of La2Ce2O7 hollow microspheres: same as (2) in Example 3. Figure 7 The SEM image of the La2Ce2O7 hollow microspheres of this comparative example shows that the obtained La2Ce2O7 hollow microspheres have crater-like shapes and large holes in the middle.

[0059] The above-mentioned embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. For ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A La x Ce (1-x) O (2-0.5x) A method for preparing hollow microspheres, characterized in that: The method comprises the following steps: 1) Slurry preparation: deionized water, dispersant and La x Ce (1-x) O (2-0.5x) The powders are mixed and ground, and the pH value of the system is maintained during the grinding process. After the grinding is completed, a binder is added, and after high-speed dispersion, a slurry required for spray granulation is obtained, wherein x=0, 0.36 or 0.5; 2) Preparation of hollow microspheres: The slurry is uniformly transported to a spray granulator for spray granulation, and the hollow microspheres are collected and then burned to obtain La x Ce (1-x) O (2-0.5x) Hollow microspheres.

2. The preparation method according to claim 1, characterized in that: The dispersant in step 1) is ammonium polyacrylate, and the pH of the system is maintained at 9 during the grinding process.

3. The preparation method according to claim 1, characterized in that: The grinding process was stopped when the powder particle size was less than 500 nm.

4. The preparation method according to claim 1, characterized in that: The La x Ce (1-x) O (2-0.5x) Powder is CeO2, La 0.36 Ce 0.64 O 1.82 and one of La2Ce2O7.

5. The preparation method according to claim 1, characterized in that: In step 1), the binder is one of polyvinyl alcohol (PVA) and octylphenol polyoxyethylene ether (Triton X-100).

6. The preparation method according to claim 1, characterized in that: La x Ce (1-x) O (2-0.5x) The mass ratio of powder, deionized water and dispersant is 1:0.5-1:0.001, La x Ce (1-x) O (2-0.5x) The mass ratio of powder to PVA is 1:0.02, La x Ce (1-x) O (2-0.5x) The mass ratio of powder to Triton X-100 is 1:0.

06.

7. The preparation method according to claim 1, characterized in that: In step 2), the inlet temperature of the spray granulator is controlled at 110°C-130°C.

8. The preparation method according to claim 1, characterized in that: In step 2), the calcination temperature of CeO2 is 800°C, and the 0.36 Ce 0.64 O 1.82 And the calcination temperature of La2Ce2O7 is 1000℃-1200℃.

9. La prepared by the method according to any one of claims 1 to 8 x Ce (1-x) O (2-0.5x) Hollow microspheres, characterized in that The La x Ce (1-x) O (2-0.5x) The bulk density of hollow microspheres is 1.30-1.35g / cm 3 , particle size D 50 The wall thickness is 15-25μm, the wall thickness is 100-150nm, the compressive strength is 4.5-6.5Mpa, and the room temperature thermal conductivity is 0.05-0.06W / (m·K).

Citation Information

Cited By

  • Reflective thermal insulation coating and preparation method thereof, and coating and preparation method thereof

    CN121851815A